Analisis Status Gizi dan Kebutuhan Kalori pada Peserta Didik di SMP Negeri 4 Tabanan - I Gusti Nyoman Agung Mahadiptha; Hendra Mashuri; Peby Gunarto (Journal of Innovative and Creativity, 2025)
The study purpose was to determine the nutritional status and calorie requirements of students at SMP Negeri 4 Tabanan. The background of this research arises from the absence of a systematic nutritional status monitoring program in schools, while indications of nutritional problems such as fatigue, lack of concentration, and changes in body weight have begun to appear among students. This study aims to provide an overview of the students’ nutritional conditions and energy needs as a foundation for health and nutrition interventions in schools. Materials and methods.This research employed a descriptive quantitative approach. The sampling technique used Slovin’s formula, resulting in a total sample of 120 students from a population of 171. Data were collected through anthropometric measurements, including body weight and height, which were used to calculate Body Mass Index (BMI) to determine nutritional status. Additionally, daily calorie requirements were calculated using the Basal Metabolic Rate (BMR) formula, considering gender, age, and physical activity levels of the students. Results.The results showed that most students were categorized as undernourished (51%), while 38% had normal nutritional status, and 11% were classified as overweight or obese. The average daily calorie requirement was approximately 2,659.52 kcal, with the macronutrient composition consisting of 399 g carbohydrates, 74 g fat, and 100 g protein per day. The descriptive analysis indicated that the imbalance between energy intake and expenditure was a key factor influencing nutritional variations among students. Conclusions.The study emphasizes the importance of balanced nutrition education and lifestyle habits that align with students’ energy needs. The findings are expected to serve as a reference for schools in developing nutritional monitoring programs, balanced diet education, and healthy lifestyle promotion. Future studies are recommended to include dietary pattern analysis and explore the relationship between nutritional status, physical fitness, and academic performance.